Environmental impact assessment as a tool of environmental management for sustainable development - Eissa, Garoot Suleiman (2009)
This proposed paper seeks to explain the importance of Environmental Impact Assessment, as a planning and management tool, in reversing environmental degradation in countries that adopt it to improve chances of future sustainable development. Malaysia will be held as a case in point. Environmental degradation is generally attributed to sustained economic growth, growth of population and industrialization, which inevitably result in pollution and depletion of resources in the absence of effective environment management. The basic contention of the paper is that EIA, as a procedure that ensures the compatibility of proposed development projects with environmental standards and requirements should have a more positive impact on chances of sustainability of development than post-control measures that follow implementation. It interrupts the positive relationship between growth and environmental degradation.